Sri Lanka - Toward an Urban Transport Strategy for Colombo : A Technical Note - World Bank (Washington, DC, 2013)
The objective of this paper is to serve as an input into the on-going discussions concerning sectoral and cross-sectoral aspects of the strategy. Following this introduction, the second chapter provides a brief background on the region, its people, economy and the transport system. This is needed given that some readers on the Bank side will not be familiar with Colombo. The third chapter reviews the performance of the regional transport system from the point of view of its various users, and attempts to explain the findings in terms of underlying problems and issues. The fourth chapter presents, in summary form, the strategic proposals currently on the table. The fifth chapter provides a critical review of the proposals. The sixth and final chapter reviews the past involvement of the Bank in this sector, then identifies and discusses options that could be considered for future assistance, if the sector emerges as a joint CAS priority. An attempt has been made to shed a stronger light on people concerns, in addition to a traditional focus on transport regulation, infrastructure investments and traffic management. As an explicit sign of this, boxes with real-life travel stories of persons from the CMR have been sprinkled throughout the text.